Targeting social transfers in pastoralist societies: Ethiopia’s productive safety net programme revisited - Lind, Jeremy; Sabates-Wheeler, Rachel; Hoddinott, John F.; Taffesse, Alemayehu Seyoum (International Food Policy Research Institute, 2018)
In the Ethiopian highlands, the Productive Safety Net Programme (PSNP) is a successful social safety net intervention in terms of both targeting and impact. By contrast, existing studies situated in the country's lowland Afar and Somali regions suggest that PSNP targeting is beset with difficulties. This is deeply concerning given that these predominantly agro-pastoral and pastoral areas have some of the country's highest levels of poverty and food insecurity and that there is an absence of viable livelihoods outside of pastoralism in these localities. In this paper, which draws on three rounds of household survey data from 2012, 2014, and 2016, we show that there has been no meaningful improvement in targeting performance since 2010. We assess five explanations for this – resources and under-coverage; the involvement of traditional leaders in targeting; insufficient training; attitudes of program implementers; and transparency – adducing that norms regarding fairness and a lack of transparency are the most likely explanations for continued poor targeting. The PSNP experience calls into question the effectiveness of technocratic fixes as well as the appropriateness of targeting transfers in pastoralist societies.